On some Bamberg wide-field plate catalogues recently incorporated into WFPDB - Tsvetkova, K.; Tsvetkov, M.; Kirov, N.; Kalaglarsky, D.; Edelmann, Heinz; Heber, Ulrich (Astronomical and Astrophysical Transactions, 2018)
The Dr. Remeis-Sternwarte (Bamberg Observatory) hosts about 40000 astronomical photographic plates taken from the early 20th century to the mid 1970s. In an ongoing long-term project the Bamberg wide-field plate catalogues are being incorporated into the Wide-Field Plate Database (WFPDB). Here, we describe the recent integration of seven Bamberg catalogues in the framework of a project to digitize and preserve the plates, funded by the German Science Foundation. These catalogues include information about 8400 plates obtained in the period 1931-1963 with three Tessar cameras (WFPDB identifiers BAM003A, BAM003B and BAM009A), a Xenon camera (BAM006), a Vierlinser camera (BAM008), an Ernostar camera (BAM009B), and a Dogmar camera (BAM011). The plate observations aimed at investigations of variable stars in the Northern sky. Some of the cameras were first mounted on an astrograph in Bamberg in preparation for, and testing of the Bamberg large-scale project for variable star research in the Southern sky in the period 1963-1976. Currently information on 31 Bamberg plate archives containing 34200 plates from the Bamberg Northern and Southern Sky Survey can be found in the WFPDB.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Astroinformatics; Databases; Plate catalogues